ANALISIS TINGKAT PEMAHAMAN MAHASISWA AKUNTANSI TERHADAP KONSEP DASAR AKUNTANSI (STUDI EMPIRIS PADA MAHASISWA AKUNTANSI DI UNIVERSITAS INTERNASIONAL BATAM - Dian Efriyenti (PEKBIS, 2017)
In this research, the researcher tries to investigate from the Analysis of AccountingStudent's Level of Understanding on Basic Concepts of Accounting (Empirical Studyon Accounting Students at International University of Batam) With the foundation asthe guidance of all accounting practices and theories will be easily implemented.Butthe fact that accounting education has been taught In college is impressed asknowledge that only oriented to the mechanism in general, very much different whencompared with the practice faced in the field.The basic material about the basicconcepts of accounting that must be mastered by accounting students in accountingintroductory courses, namely understanding of assets, liabilities , And equity, thestudents are expected to understand all the problems that will be encountered inaccounting.The result of this study states that there is no difference to theunderstanding of assets, liabilities and Equity between students coming from SMKmajoring in Accounting, SMA IPS and SMA IPA which shows that the background ofupper middle education does not trigger different understanding of the threeconcepts.